2015
DOI: 10.1016/j.jchf.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Heart Failure in Low- and Middle-Income Countries

Abstract: Successful combination therapy for human immunodeficiency virus (HIV) has transformed this disease from a short-lived infection with high mortality to a chronic disease associated with increasing life expectancy. This is true for high- as well as low- and middle-income countries. As a result of this increased life expectancy, people living with HIV are now at risk of developing other chronic diseases associated with aging. Heart failure has been common among people living with HIV in the eras of pre- and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 93 publications
2
69
2
9
Order By: Relevance
“…45 Globally, HF is common in low-income and middle-income countries, where the burden of HIV is high and availability of ART can be limited. 46 Given these facts, health care professionals should focus on guideline-recommended HIV treatment and HF risk factor prevention (including diabetes, hypertension, renal disease, smoking, alcohol abuse and dependence, and obesity), as well as screening for HIV in individuals with new-onset HF where appropriate. 25 Developing tools designed to risk stratify HIV-infected individuals for HF will also be required.…”
Section: Discussionmentioning
confidence: 99%
“…45 Globally, HF is common in low-income and middle-income countries, where the burden of HIV is high and availability of ART can be limited. 46 Given these facts, health care professionals should focus on guideline-recommended HIV treatment and HF risk factor prevention (including diabetes, hypertension, renal disease, smoking, alcohol abuse and dependence, and obesity), as well as screening for HIV in individuals with new-onset HF where appropriate. 25 Developing tools designed to risk stratify HIV-infected individuals for HF will also be required.…”
Section: Discussionmentioning
confidence: 99%
“…In low-to-middle income countries, systolic HF remains a more important contributor to the CVD burden in PLWH, even as access to ART expands [26]. On the other hand, studies have suggested that HIV+ patients with HF are less likely to be optimally treated with antiplatelet drugs, statins, diuretics, and angiotensin-converting enzyme inhibitors/aldosterone receptor blockers (ARBs; p < 0.0001 for all comparisons) compared to uninfected patients with heart failure [4, 5].…”
Section: Heart Failure and Myocardial Diseases In Hiv-infected Patientsmentioning
confidence: 99%
“…Sin embargo, la compresión de la patogénesis de este proceso no se ha abordado de manera sistemática en estudios 23 . Hay diversas hipótesis que pueden ser sugestivas de este proceso de afección, entre estas están: replicación viral, infecciones oportunistas, influencia antirretroviral, entre otras causas.…”
Section: Falla Cardíacaunclassified
“…Las tasas de mortalidad hospitalaria, en dos países africanos, por falla cardíaca asociada a VIH alcanzaron el 15% para el año 2007 24,25 . En dos grandes estudios observacionales realizados en países de ingresos bajos y medios se informó que la falla cardíaca asociada a VIH aún es un diagnóstico muy común en estos pacientes siendo necesario una intervención más temprana 2,23,26,27 . Una hipótesis implica la toxicidad miocárdica directa viral, donde el ácido ribonucleico del VIH en altas concentraciones, es decir más de 500 copias por mL de sangre, se asocia con cerca de 2,5 veces más probabilidad de desarrollar falla cardiaca en comparación con individuos no infectados 27 .…”
Section: Falla Cardíacaunclassified